The Disparity between Normative Law and Empirical Law in the Sociology of Law in Indonesi (Hakim: Jurnal Ilmu Hukum dan Sosial, 2026)
The study aims to see how wide this gap really is between normative and empirical law, plus figuring out what causes it, and also how social change itself plays a part in shaping the connection between legal norms and everyday practices in society. Not just “what the rules say”, but also what people actually do, that kind of thing. For the method, this research uses a socio-legal approach. It blends qualitative and quantitative techniques, so the data collection becomes more grounded. Data were obtained from 150 respondents through interviews and documentation, then later processed systematically. Statistical techniques are used to keep the findings reliable and yes, to make sure the patterns are not only based on impressions. The results show that the gap between normative and empirical law is relatively high. Around 45.3% of respondents reported a low level of conformity. As for the causes, social factors account for 28% and institutional or law enforcement factors account for 26%, which both come up as the most prominent explanations. In addition, social change is found to have a significant relationship with the level of legal disparity. The contribution of this study is in reinforcing an integrative approach between normative aspects and empirical aspects in the sociology of law.